Online instructional consultation for higher education institutions in Malaysia: The system architecture - Ang, Ling Weay; Abd Razak, Abd Hadi (The Society of Digital Information and Wireless Communications, 2011)
Evolution of communication technologies at present gives impetus to researchers and practitioners by simply put the computer-mediated communication tools on their telementoring application without really understand its potential benefits. This causes several issues and challenges confronting existing telementoring program which are: (a) miscommunication due to lack of nonverbal cues, (b) the need of competency in written communication and technical skills, and (c) document recording, retrieving and reviewing. Thus, in this paper, the focus is the design and development of Online Instructional Consultation (OICon) system for student and lecturers of higher education institutions. Hybrid modes of synchronous and asynchronous communication that provide nonverbal and verbal cues are incorporated in Online Instructional Consultation (OICon) system to compensate the identified issues and challenges. We also focus on recording, retrieving and reviewing of recorded consultation document and management is also emphasized.The multimedia communication components from e-consultation model of financial and telemedicine context are adapted. The general structure, modules of OICON system, multimedia communication components, and communication server are illustrated and the potential benefits of OICon system are presented.